Benefits, challenges, and strategies related to using presumptive recommendations for HPV vaccination: A qualitative study with rural and non-rural-serving primary care professionals - Olufeyisayo O. Odebunmi; Lisa P. Spees; Caitlin B. Biddell; Tatenda Yemeke; Juan Yanguela; Colleen Higgins; Melissa B. Gilkey; Sachiko Ozawa; Stephanie B. Wheeler (Taylor & Francis Group, 2024)
ABSTRACTHPV vaccination coverage remains far below the national target of 80% among US adolescents, particularly in rural areas, which have vaccine uptake rates that are 10% points lower than non-rural areas on average. Primary care professionals (PCPs) can increase coverage by using presumptive recommendations to introduce HPV vaccination in a way that assumes parents want to vaccinate. Through semi-structured interviews, we explored PCPs' experiences and perceptions of using presumptive recommendations in rural- and non-rural-serving primary care clinics in North Carolina. Thematic analysis revealed that most PCPs in rural and non-rural contexts used presumptive recommendations and felt the strategy was an effective and concise way to introduce the topic of HPV vaccination to parents. At the same time, some PCPs raised concerns about presumptive recommendations potentially straining relationships with certain parents, including those who had previously declined HPV vaccine or who distrust medical authority due to their past experiences with the healthcare system. PCPs dealt with these challenges by using a more open-ended approach when introducing HPV vaccination to parents. In conclusion, our findings suggest that PCPs in both rural and non-rural settings see value in using presumptive recommendations to introduce HPV vaccination, but to adequately address concerns and ensure increased HPV vaccine uptake, PCPs can use simple and culturally sensitive language to ensure fully informed consent and to maintain parental trust. And to further strengthen HPV vaccine discussions, PCPs can utilize other effective HPV communication techniques, like the Announcement Approach, in discussing HPV vaccinations with hesitant parents.